The affect of person-organizational fit, organizational climate and organizational citizenship behavior toward Police performance in Kerinci - Ronal Regen; Rizky Ramadhani Syahril; Anggi Dwi Saputra Maha; Evoni Lukiawati; Siliswati Siliswati (Institute of Computer Science (IOCS), 2023)
This study aims to see the effect of (1). Person-Organizational Fit on the performance of employees at the Kerinci Police. (2). Organizational climate on employee performance at the Kerinci Police. (3). Organizational citizenship behavior on employee performance at the Kerinci Police. (4). Person-Organizational fit, climate and organizational citizenship behavior have a joint effect on employee performance at the Kerinci Police Station. The population in this study were all 476 employees at the Kerinci Police. And the technique of determining the number of samples taken as respondents by determining the number of samples taken as respondents using the Slovin formula. So the number of samples in this study amounted to 217 people who are Kerinci Police. The results of this study indicate that (1) Person organizational fit has a positive influence on employee performance at the Kerinci Police Station. (2) Organizational climate has a positive influence on employee performance at the Kerinci Police. (3) Organizational citizenship behavior has a positive influence on employee performance at the Kerinci Police. (4) Person organizational fit work, organizational climate, organizational citizenship behavior jointly have a positive effect on employee performance at the Kerinci Police Station.